Acute generalized exanthematous pustulosis: clinical characteristics, etiologic associations, treatments, and outcomes in a series of 28 patients at Mayo Clinic, 1996–2013. (13th January 2017) - Alniemi, Dema T.; Wetter, David A.; Bridges, Alina G.; el‐Azhary, Rokea A.; Davis, Mark D. P.; Camilleri, Michael J.; McEvoy, Marian T.
Abstract: Background: Acute generalized exanthematous pustulosis (AGEP) is a rare skin condition typically caused by medications. The objective of this study was to examine the clinical features, causes, and outcomes of AGEP at a sole tertiary care center. Methods: A retrospective review of patients with AGEP (European Study of Severe Cutaneous Adverse Reactions score of ≥ 5) seen at Mayo Clinic (Rochester, MN, USA) between January 1, 1996, and December 31, 2013, was conducted. Results: Of 28 patients (mean age at onset: 56 years), 17 (61%) were women. The development of AGEP was attributed to medications in 25 patients (89%), with clindamycin the most common culprit (six patients). Three patients (11%) had mucous membrane involvement, and 21 (75%) showed systemic involvement. Ten patients (36%) received systemic corticosteroids for treatment of AGEP. Skin findings resolved within 15 days in 26 patients (93%) (mean time to resolution: 7.6 days). In three patients (11%), generalized skin eruptions or dermatitis developed weeks to months after the resolution of AGEP. Twenty‐four patients (86%) had a personal history of drug reactions before the development of AGEP. Conclusions: A previous history of drug reactions and clindamycin causation were more common in the present cohort than in prior reports. A small subset of patients experienced new‐onset non‐AGEP skin eruptions within a few months of the resolution of AGEP.